A novel wideband bandpass filter based on CSRR‐loaded substrate integrated folded waveguide. Issue 6 (12th February 2020) - Yang, Ling; Xu, Feng; Qiang, Jingxia; Liu, Shui; Zhan, Junlin
Abstract: A novel wideband bandpass filter based on folded substrate integrated waveguide (FSIW) is presented in the article. Five square complementary split‐ring resonators (CSRRs) are etched in the middle layer of the FSIW. By adjusting the physical size of the CSRR structure, the resonant frequency of the CSRRs can be tuned at the same time and the stopband performance can be changed. As transverse electromagnetic (TEM) mode can be transmitted in the stripline, FSIW excited by stripline shows wider passband than that excited by microstrip line directly. To achieve perfect impedance matching, two microstrip lines to stripline transitions are added in two ports of the filter. The proposed bandpass filter exhibits compact size, high selectivity, good stopband rejection, lower radiation loss, and wideband performances. The measured results show that the fractional bandwidth of the filter is about 35.5%. The measured return loss is better than 15 dB from 4.84 GHz to 6.90 GHz, and the insertion loss is less than 1.2 dB. The comparison between the simulated results and the measured ones validate the possibility of the technology that combines the FSIW and CSRR.